2010
DOI: 10.1038/ja.2010.108
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion of AS1387392: bioconversion studies involving Amycolatopsis azurea JCM 3275

Abstract: We screened actinomycetes capable of converting AS1387392 to AS1429716 and identified those strains capable of hydroxylation. Amycolatopsis azurea JCM 3275 was found to be a particularly efficient strain, capable of converting AS1387392 to AS1429716, with a yield of 44% after 9 h. This strain can metabolize not only the hydroxylation of phenylalanine at the meta and para positions but also the reduction of hydroxyketones, as shown by the isolation of bioconversion products. Examination of more suitable convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…12 AS1429716 potently inhibited histone deacetylase activity with an IC 50 value of 22 nM, demonstrating this compound to be as potent as AS1387392 (IC 50 ¼22 nM). 9,12 Given that several biochemical analyses indicated that cytochrome P450 was responsible for this hydroxylation, we attempted to clone a gene encoding bacterial cytochrome P450 that would catalyze the hydroxylation of AS1387392 to AS1429716. Furthermore, to confirm its function, we attempted to produce its expression in a Streptomycetes host.…”
Section: Introductionmentioning
confidence: 99%
“…12 AS1429716 potently inhibited histone deacetylase activity with an IC 50 value of 22 nM, demonstrating this compound to be as potent as AS1387392 (IC 50 ¼22 nM). 9,12 Given that several biochemical analyses indicated that cytochrome P450 was responsible for this hydroxylation, we attempted to clone a gene encoding bacterial cytochrome P450 that would catalyze the hydroxylation of AS1387392 to AS1429716. Furthermore, to confirm its function, we attempted to produce its expression in a Streptomycetes host.…”
Section: Introductionmentioning
confidence: 99%
“…Changes of the code name of the reportedly novel immunosuppressive cyclic tetra-peptide published in The Journal of Antibiotics, November issue, 63, 633-636 (2010), and the following three articles [1][2][3] were not clearly explained. In addition, citations to the synthetic preparation and testing of those compounds were not included.…”
mentioning
confidence: 99%